Evaluasi Program Kepemudaan oleh Pemerintah Provinsi Sumatera Barat dalam Meningkatkan Kualitas Pemuda di Era Disrupsi - Febrianto, Rizki; Frinaldi, Aldri (PUBLICNESS: Journal of Public Administration Studies, 2023)
The advancement of technology has led to a shift in skill demands, and young people must be able to develop new skills that are relevant to the market needs. Additionally, they also face risks such as job uncertainty, industry disruption, and the digital divide among those with access. This research aims to evaluate youth programs conducted by the West Sumatra Provincial Youth and Sports Office (DISPORA) in improving the quality of the youth. The study employs a qualitative research method using the evaluation analysis of the CIPP (Context, Input, Process, Product) Model and SWOT (Strengths, Weaknesses, Opportunities, Threats) analysis. The object of this research is the youth programs implemented by the West Sumatra Provincial Youth and Sports Office, by collecting data and information related to the programs, such as activity reports, budgets, and interview results with stakeholders from the West Sumatra Provincial Youth and Sports Office. The findings indicate that the youth programs implemented have not fully succeeded in enhancing the creativity of the youth, as the focus of the programs mostly centers around character development. Moreover, there are several obstacles, such as the lack of support from local governments, the programs remaining lecture-based (traditional), and the apparent lack of collaboration with the private sector.